Preliminary Assessment of Electromagnetic Field Effects Induced by High and Medium Voltage Power Lines on Carbon Assimilation in Maize and Sunflower Crops - Viorel Fătu; Vasilică Savu; Agripina Șapcaliu; Roxana Zaharia; Iulian Voicea (Scientific Papers Animal Science and Biotechnologies)
The purpose of the study is to analyze the impact of EMFs on the carbon footprint of agricultural crops, using sunflower (Helianthus annuus) and maize (Zea mays). The objective of the research is to develop an experimental model for evaluating the influence of electromagnetic fields generated by medium-voltage (1–35 kV) and high-voltage (35–275 kV) power lines on maize and sunflower crops. Considering that soil nutrient concentrations can vary significantly, assessing the impact of electromagnetic fields on crops, based solely on biomass accumulation, is challenging. Therefore, this study proposed the hypothesis that, under a constant atmospheric concentration of carbon dioxide, the total organic carbon content within plants should remain proportionally constant, regardless of the soil's nutritional conditions. The study was conducted in DB and Iasi (IS) counties for high-voltage lines, in Prahova (PH) county for medium-voltage lines and in Calarasi (CL) county as a control location without electromagnetic influences. The carbon content analysis in plants indicated that crops assimilate less carbon in areas exposed to high-voltage power lines in and sunflower and that medium-voltage lines positively influence carbon assimilation in sunflower. A deeper understanding of EMF-induced effects on the carbon cycle may provide a scientific foundation for adaptive strategies and optimization of agricultural practices, aiming to minimize environmental risks while maximizing soil capacity as an efficient carbon reservoir.